Expand this⬆️
Using the formula of-
(a-b)^3
Attachments:
![](https://hi-static.z-dn.net/files/dfd/436feb47c62acd2b907989cc2cbb21cc.jpg)
Answers
Answered by
7
AnSwEr
- (x-y+2z)³
- break it into (a-b)³
we know that (a+b)³
(a+b)³=a³+b³+3ab(a+b)
Let x-y = a
Then
(a+2z)³ =a²+4z²+6az(a+2z)
¶utying the value of a in the Polynomial
________________________
=>(a+2z)³ =a³+4z³+6az(a+2z)
=>(x-y+2z)² = (x-y)³+4z³+6(x-y)z(x-y+2z
=>(x-y+2z)² = x³-y³-3xy(x-y)+4z³+6(x-y)z(x-y+2z
=>(x-y+2z)² = x³-y³-3xy(x-y)+4z³+6zx-6yz(x-y+2z)
=>=>(x-y+2z)² = x³-y³-3xy(x-y)+4z³+6zx-6yz(x-y+2z)
________________________
Similar questions